2016
DOI: 10.1007/s00520-016-3248-5
|View full text |Cite
|
Sign up to set email alerts
|

When fear of cancer recurrence becomes a clinical issue: a qualitative analysis of features associated with clinical fear of cancer recurrence

Abstract: While features of clinical FCR found in this analysis such as intrusive thoughts, distress and impact on functioning confirmed previous FCR research, other features spontaneously emerged from the interviews including "death-related thoughts," "feeling alone," and "belief that the cancer will return." The participants' descriptions of cancer-specific fear and worry suggest that FCR is a distinct phenomenon related to cancer survivorship, despite similarities with psychological disorders (e.g., Anxiety Disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 29 publications
5
76
1
1
Order By: Relevance
“…As coping response is guided by metacognition, intensified negative beliefs about worry may counterproductively trigger disengagement coping to manage emotional distress rather than the actual trigger itself, leading to the development and maintenance of clinical FCR. A previous qualitative study reported that disengagement coping strategies such as avoidance and distraction, emotion‐control strategies, were more common among cancer survivors with clinically significant FCR than those without …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As coping response is guided by metacognition, intensified negative beliefs about worry may counterproductively trigger disengagement coping to manage emotional distress rather than the actual trigger itself, leading to the development and maintenance of clinical FCR. A previous qualitative study reported that disengagement coping strategies such as avoidance and distraction, emotion‐control strategies, were more common among cancer survivors with clinically significant FCR than those without …”
Section: Discussionmentioning
confidence: 99%
“…Their associations with FCR generally disappear in multivariate analyses suggesting a minor role in FCR . Younger age seems somewhat related, but psychological factors predominantly determine FCR. One potential mechanism involves maladaptive information processing styles .…”
Section: Introductionmentioning
confidence: 93%
“…Recruitment continued until 20 participants with low FCR and 20 with high FCR completed the study. Differences between participants and nonparticipants are reported elsewhere . The Ottawa Hospital ethics board approved this study, and all participants gave informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative interviews with De Vries et al found that 74% of cancer patients said they thought about the possibility of recurrence every month, with one of them even thinking about recurrence several times a week. Patients with FCR often have the following characteristics: Thoughts associated with death, feeling lonely, believing that cancer will recur, uncertain experiences, the emergence of uncontrollable thoughts and images associated with cancer, and the thoughts often occur every day and last longer than 30 min . The previous studies have confirmed that FCR is concurrent with a significantly lower quality of life (QOL), functional impairments, and increased use and cost of health care.…”
Section: Introductionmentioning
confidence: 99%
“…In recently published studies, a variety of factors were found to be associated with the cancer patients’ FCR level. Demographic characteristics such as female gender, young age, living apart or divorce, a higher level of education, and no children have been reported to be related to higher FCR.…”
Section: Introductionmentioning
confidence: 99%